A Decade of Close-to-Nature Transformation Alters Species Composition and Increases Plant Community Diversity in Two Coniferous Plantations - Ming, Angang; Yang, Yujing; Liu, Shirong; Nong, You; Tao, Yi; Zeng, Ji; An, Ning; Niu, Changhai; Zhao, Zhang; Jia, Hongyan; Cai, Daoxiong (Frontiers in Plant Science, 2020)
Close-to-nature transformation silviculture is a promising approach to meet the criteria for sustainable forestry. To explore the effects of close-to-nature transformation on community structure and plant diversity in Pinus massoniana and Cunninghamia lanceolatas pure plantations, four stands were selected, including close-to-nature transformed stand of P. massoniana (PCN) and its unimproved pure stand (PCK), and close-to-nature transformed stand of C. lanceolata (CCN) and its unimproved pure stand (CCK). Plant diversity and community structure in the four stands were investigated before and after a decade of close-to-nature transformation. After the close-to-nature transformation, the plant diversity and community structure were significantly altered. Compared with control stands, the transformation increased the species richness and diversity of the tree layer and the whole community, while did not significantly affected the shrub and herb diversity. The species richness in the tree layer in the P. massoniana and C. lanceolata plantations was 2.1 and 2.8 times that of their corresponding control. Species composition and important value of each species were altered in the tree, shrub and herb layers. The close-to-natural transformation lowered the community dominance and the important value of P. massoniana and C. lanceolate. The advantage position of single species in the community was weakened by the forest transformation. The plant community became diversified and uniformly distributed. The enhanced community species diversity was derived from the increase in the tree diversity. These results indicated that close-to-nature transformation increased the forest plant diversity and optimized the community structure. The close-to-nature transformation plays a positive role in coniferous plantation ecosystem structure.